Dampak Penerapan Penghentian Penuntutan Berdasarkan Keadilan Restoratif terhadap Korban dan Pelaku - Airlangga Surya Nagara; Elizabeth Ayu Puspita Adi; Reza Ilham Maulana (Journal of Law, Society, and Islamic Civilization, 2025)
The paradigm shift in Indonesian criminal law toward restorative justice (RJ) reflects an effort to address the shortcomings of the retributive system, which focuses solely on punishment. The central issue in this study is how the policy of terminating prosecution based on restorative justice affects the position of victims and offenders within the criminal justice system. This research aims to analyze the normative and empirical impacts of such policy on substantive justice, as well as to identify the potential and challenges of its implementation. The method employed is normative juridical, using both conceptual and case approaches, supported by systematic literature analysis guided by the PRISMA framework. The findings indicate that RJ provides a space for dialogue-based resolution, reduces over-criminalization, and strengthens offender reintegration without negating victims’ rights. However, its practical application still faces obstacles such as disparities in institutional understanding, potential pressure on victims, and regulatory inconsistencies. Case studies in East Flores and Tojo Una-Una reaffirm the effectiveness of RJ in strengthening social cohesion. It is concluded that RJ is not merely an alternative, but an integral component of criminal law reform in Indonesia that is just, inclusive, and transformative, aligned with local values, the principle of opportunity, and the theories of Zehr and Braithwaite.